1991
DOI: 10.1115/1.2897265
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Velocity, Velocity Fluctuation, Density, and Stresses in Chute Flows of Granular Materials

Abstract: Experiments on continuous, steady flows of granular materials down an inclined channel or chute have been conducted with the objectives of understanding the characteristics of chute flows and of acquiring information on the rheological behavior of granular material flow. Two neighboring fiber-optic displacement probes provide a means to measure (1) the mean velocity by cross-correlating two signals from the probes, (2) the unsteady or random component of the particle velocity in the longitudinal direction by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 0 publications
5
37
1
2
Order By: Relevance
“…For all exit openings, it was observed that the corresponding mean flow speed was higher for the dyed particles than for the clear particles. The reason for this phenomenon is not clear, though it might be due to the exit hopper condition (Nguyen, Brennen & Sabersky 1979;Brennen & Pearce 1978). Figure 7 compares the normalized transverse fluctuation velocity distributions, at three representative transverse locations, for the rough and smooth wall conditions.…”
Section: Velocity Profiles : Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all exit openings, it was observed that the corresponding mean flow speed was higher for the dyed particles than for the clear particles. The reason for this phenomenon is not clear, though it might be due to the exit hopper condition (Nguyen, Brennen & Sabersky 1979;Brennen & Pearce 1978). Figure 7 compares the normalized transverse fluctuation velocity distributions, at three representative transverse locations, for the rough and smooth wall conditions.…”
Section: Velocity Profiles : Observations and Discussionmentioning
confidence: 99%
“…Although the granular temperature is a key property in the analytical studies, there have been few attempts to measure its magnitude in experimental studies. Ahn, Brennen & Sabersky (1991) and Hsiau & Hunt (1993a) only measured the streamwise fluctuation velocity 2 V. V. R. Natarajan, M. L. Hunt and E. D. Taylor component using fibre-optic probes. Drake (1991) measured both fluctuation velocity components in a two-dimensional, high-shear-rate low-density flow down an inclined chute, using high-speed photographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, most industrial conditions involve flat boundaries, as well as natural flows occurring on smooth bed rocks at the scale of the grains. Surprisingly very few studies [2,11,[25][26][27][28][29][30][31][32] have considered this more common case of flat frictional surfaces. Early experimental works mention increased flow velocity and sliding conditions at the boundaries compared to the bumpy walls case [11].…”
Section: The State Of the Art On Granular Flows Down Inclined Chamentioning
confidence: 99%
“…It is also common in geophysical situations where rock avalanches, landslides and pyroclastic and debris flows are natural events consisting in large-scale flows of grains [1,2,3]. Many chute flow experiments have been carried out and different configurations have been used, changing the boundary conditions from smooth [4,5] to rough [6], and using different kinds of materials [7,8,9,10] without any systematic investigation.…”
Section: Introductionmentioning
confidence: 99%